The Performance Evaluation of Equity Mutual Funds in China - Zhang, Ying (2007)
Chinese mutual funds are growing rapidly, which have achieved a phenomenal amount of return in 2006. However, figures may lead to an overoptimistic view of Chinese mutual fund market; hence overestimate fund managers' performance. This study attempts to provide a true and fair opinion in this regard with realistic data.